The Case of Bradycardia Occured in the Setting of Hyperkalemia in a Patient in Ambulatory Hemodialysis Department - G. A. Ignatenko; G. G. Taradin; A. E. Bagry; I. V. Rakitskaya; K. E. Mogilevskaya; V. I. Merkuriev; A. L. Khristulenko (Архивъ внутренней медицины, 2021)
The presented article contains the clinical observation of bradycardia development in 64-year-old patient with chronic kidney disease who was in ambulatory treatment at the hemodialysis department. During electrocardiogram recording an arrhythmia was detected as a junctional rhythm. The specific changes on electrocardiogram, presence of risk factors, and data of additional collection of history disease allowed purposing the development of dangerous condition — hyperkalemia. The diagnosis was confirmed after detection of the serum potassium level. This case illustrates the necessity to consider the possibility of hyperkalemia in patients with chronic kidney diseases including those who undergoing hemodialysis treatment. Relevant clinical manifestations and changes on the electrocardiogram require the urgent assessment of the serum potassium level for timely and adequate correction of the electrolyte disorder.